Physiotherapeutic management of patients with SMA: a questionnaire-based online survey among physiotherapists within the SMArtCARE network - Vogt, Sibylle; Voigt-Müller, Cornelia; Rochau-Trumpp, Heidi; Malm, Eva; Roland-Schäfer, Doris; Roetmann, Gerda; van Vugt, Judith; Stein, Sabine; Kirschner, Janbernd; Pechmann, Astrid (Journal of neuromuscular diseases, 2025)
Background and objectives: Disease-modifying treatments (DMT) have dramatically changed phenotypes in patients with spinal muscular atrophy (SMA). Because publications regarding standards of care were published before DMTs emerged, detailed recommendations and guidelines for physiotherapeutic management are still lacking. The objective of this study was to map the physiotherapeutic management of patients with SMA within the SMArtCARE network, a disease-specific registry for patients with 5q-SMA with 83 participating centers in Germany, Switzerland, and Austria. - Methods: An online survey using a modified Delphi approach was conducted among physiotherapists with two questionnaire rounds between June 2022 and June 2023. Seven physiotherapeutic experts developed and revised the questionnaires focusing on the main topics of stretching, positioning, mobility and exercise, and chest physiotherapy. The second questionnaire was based on eight different case studies. - Results: The second questionnaire was sent to 148 participants with a response rate of 28%. Most of the physiotherapists were well experienced in treating SMA patients. There was a strong consensus that home-based stretching should be used in pediatric patients with contractures regardless of their motor function. Muscle strengthening training was considered to be essential for all sitters and for walkers with moderate motor function restriction by a strong consensus. For all patients with respiratory involvement there was a consensus for prophylactic respiratory therapy. - Conclusion: Our results describe the current physiotherapeutic management and recommendations within the SMArtCARE network. These findings highlight the need for an individualized approach, and the necessity of developing and adjusting existing guidelines.
Zuerst online veröffentlicht: 19. August 2025
Gesehen am 15.01.2026